(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
The article presents the results of studies of the influence of the distance between different grates on the efficiency of cleaning equipment. It is known that during the cleaning process, the distance between the grates of the grate affects the cleaning efficiency of the equipment.